PENERAPAN TEKNIK POLA RUDIMENTS PADA KELOMPOK DRUMBAND DI SMA NEGERI 01 LEBONG BENGKULU - Imam Gozali; Harisnal Hadi (Universitas Negeri Padang, 2025)
This research is motivated by the fact that many members of the drum band at SMAN 01 Lebong are still unable to master basic techniques such as holding the sticks, placing strikes on the membrane, and the dynamics of strikes. This study aims to describe the application of rudiment patterns in the extracurricular drum band group at SMAN 01 Lebong. This type of research is action research with stages of planning, implementation, and evaluation. The population of this study is students involved in the extracurricular activities of the drum band at SMAN 01 Lebong with a sample of 50 people. Data was collected through observation, interviews, and documentation. The steps in data analysis are to collect data, describe data and draw conclusions from data. The research results show that the application of the rudimentary pattern technique using a 4/4 rhythm is very effective for training members of the drum band using single stroke and double stroke techniques. The use of rudimentary pattern techniques for percussion instruments in the SMA Negeri 01 Lebong drum band can provide specific understanding and knowledge regarding the proper way to play percussion instruments.